Comparison of the clinical features of human bocavirus and metapneumovirus lower respiratory tract infections in hospitalized children in Suzhou, China - Tang, Xifeng; Dai, Ge; Wang, Ting; Sun, Huiming; Jiang, Wujun; Chen, Zhengrong; Yan, Yongdong (Frontiers in Pediatrics, 2023)
Objective: We compared the clinical data of hospitalized children with lower respiratory tract infections caused by human bocavirus (HBoV) and human metapneumovirus (hMPV). Methods: In total, 8430 children admitted to the Department of Respiration, Children’s Hospital of Soochow University for lower respiratory tract infections from January 2017 to October 2021 were enrolled. Seven common respiratory viruses, including respiratory syncytial virus, influenza virus A, influenza virus B, parainfluenza virus (PIV) I, PIV II, PIV III, and adenovirus, were detected by direct immunofluorescence assay, whereas human rhinovirus and hMPV were detected by reverse transcription-polymerase chain reaction. Mycoplasma pneumoniae (MP) and HBoV were detected by real-time fluorescence quantitative polymerase chain reaction. Bacteria was detected in blood, nasopharyngeal secretion, bronchoalveolar lavage specimen or pleural fluid by culture. Results: The detection rate of HBoV was 6.62%, whereas that of hMPV was 2.24%. The detection rate of HBoV was significantly higher in children aged 1 to <3 years than in other age groups. The epidemiology of both HBoV and hMPV has changed because of the impact of the novel coronavirus. The HBoV mixed infection rate was 51.6%, which was similar to that for hMPV mixed infection (44.4%). Comparing clinical characteristics between HBoV and hMPV single infection, the median age of children was 17 months in the HBoV group and 11 months in the hMPV group. In the HBoV single infection group, 31 patients (11.5%) had finger pulse oxygen saturation of less than 92% on admission, 47 (17.4%) had shortness of breath, and 26 (9.6%) presented with dyspnea. Meanwhile, four patients (3.8%) in the hMPV single infection group had finger pulse oxygen saturation of less than 92% on admission, eight (7.6%) displayed shortness of breath, and three (2.9%) had dyspnea. The proportion of patients requiring mechanical ventilation and the rate of PICU admission were higher in the HBoV group. Conclusion: The prevalence of HBoV infection is higher than that of hMPV infection in children with lower respiratory tract infection, and HBoV is more likely to cause severe infection than hMPV. Public health interventions for COVID-19 outbreaks have affected the prevalence of HBoV and hMPV.